Impact of Age and Subscapularis Tendon Reparability on Return to Recreational Sports Activities and 2-Year Outcomes After Reverse Total Shoulder Arthroplasty. Issue 10 (10th October 2019) - Godin, Jonathan A.; Pogorzelski, Jonas; Horan, Marilee P.; Lacheta, Lucca; Hussain, Zaamin B.; Altintas, Burak; Frangiamore, Salvatore; Mannava, Sandeep; Fritz, Erik M.; Millett, Peter J.
Background: As the indications for reverse total shoulder arthroplasty (RTSA) have continued to expand, the average age of patients undergoing RTSA has decreased. Purpose/Hypothesis: The purpose of this study was to report the minimum 2-year outcomes after RTSA and to evaluate the impact of surgical variables on outcomes. We hypothesized that younger patients, patients with larger glenosphere, and patients with irreparable subscapularis tendons would experience worse subjective patient-reported outcome scores (PROS) and that younger patients and those with a reparable subscapularis would demonstrate a higher rate of return to recreational sports activities. Study Design: Cohort study; Level of evidence, 3. Methods: Patients who underwent RTSA by a single surgeon between November 2005 and September 2014 were considered for this study. Patient characteristics, surgical details, PROS, and rates of return to recreational sports activity were prospectively collected and retrospectively reviewed. We assessed correlations between PROS and both patient age and subscapularis reparability. PROS collected included the American Shoulder and Elbow Surgeons (ASES) score, Short Form 12 (SF-12), Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) score, Single Assessment Numeric Evaluation (SANE), and postoperative patient satisfaction. Results: A total of 110 patients with an average age of 68.0 years (range, 45-87 years) were included. Minimum 2-year follow-up was obtained in 94 patients (85.4%), with a mean follow-up of 3.6 years (range, 2.0-9.3 years). The subscapularis was reparable in 58 patients (57.4%). All PROS significantly improved from pre- to postoperatively ( P < .001). The median patient postoperative satisfaction was 9 out of 10 (range, 1-10). Increasing patient age was correlated with significant improvements in QuickDASH and ASES scores. Postoperatively, 76.1% (67/88) of patients were able to return to recreational sports activity. However, of those who did return, 68.2% indicated that they had to modify their activity in some way. Glenosphere size was not significantly associated with PROS or the rate of return to recreational sports activity, but patients with reparable subscapularis tendons demonstrated higher PROS and return to activity rates. Conclusion: Patients who had a reparable subscapularis tendon showed a significantly higher rate of return to recreational sports activity than patients who had a irreparable subscapularis tendon. Older age was correlated with greater improvement in several, although not all, patient-reported outcome measures. Glenosphere size was not significantly associated with higher PROS or rate of return to recreational sports activity.